(untitled) (Вісник: Міжнародні відносини, 2025)
Abstract. This article explores the potential of investments in the cryptocurrency segment, focusing on the factors driving this resurgence, the evolving landscape of decentralized finance (DeFi), and the long-term prospects for investors. Decentralized finance has emerged as one of the most promising sectors within the cryptocurrency ecosystem. By leveraging smart contracts and blockchain technology, DeFi platforms offer financial services without intermediaries, enabling users to lend, borrow, trade, and invest with unprecedented ease and transparency. The year 2023 marked a significant turning point for the cryptocurrency market, as it emerged from what many had dubbed the "cryptowinter." The cryptowinter of 2022 was triggered by a combination of macroeconomic challenges, including rising interest rates, inflationary pressures, and the collapse of major crypto entities like FTX. This period, characterized by declining asset prices, reduced investor sentiment, and widespread uncertainty, tested the resilience of both the industry and its participants. These events led to a loss of trust among retail and institutional investors alike. However, as the cryptowinter waned, new opportunities began to surface, revealing the untapped potential of investments in the cryptocurrency segment. Yet, as 2023 unfolded, the market demonstrated remarkable recovery capabilities. Despite market downturns, institutions continued to explore blockchain technology. In 2023, we witnessed greater participation from traditional financial players, such as banks and hedge funds, who recognized the transformative potential of cryptocurrencies and DeFi. Key words: investments in the cryptocurrency segment, landscape of decentralized finance, blockchain technology, market volatility, regulation, «cryptowinter», іnstitutional аdoption, yield opportunities, investment funds, Bitcoin, ETF